Optimal Shear Wall Placement for Seismic Performance: A Comparative Study of Building Codes - Kamal Hosen (Computational Engineering and Physical Modeling)
Shear walls are one of the most popular lateral load-resisting methods used in high-rise structures. Major design factors against structural collapse in RC buildings include lateral stresses (wind, seismic). Notably, in Bangladesh, shear walls are strategically integrated into various locations to enhance both the structural rigidity and aesthetic appeal of buildings.  The optimal placement for a building's shear wall is not specified in the Bangladesh National Building Code (BNBC).This study addresses this gap by thoroughly analyzing sixteen structures according to the guidelines of four different building codes. Four buildings with different shear wall locations, such as without shear wall, the shear wall at the periphery symmetrically, the shear wall at the corner symmetrically, and the box shear wall at the core of the building have been analyzed by structural analysis and design software ETABS. By contrasting the displacement, narrative drift, story shear, and story stiffness, the outcomes are evaluated. According to the calculations, the best way to lessen displacement and story drift is to symmetrically put a shear wall at the centre of the structure. The structure may be stiffer at the center than it is elsewhere due to the symmetrical shear wall. The study's conclusions could serve as a useful guide for Bangladeshi engineers in practice.